HEALTH EXPENDITURE AND ECONOMIC GROWTH NEXUS IN NIGERIA: DOES INSTITUTIONAL QUALITY MATTER? - Keghter, K Kur; Ogbonna, Oliver E; Eze, Afamefuna A (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
Institutional quality is considered to be a determining factor in enhancing the growth of any economy. This paper examines the role of institutional quality in growth enhancement and the precise role it plays through the channel of health expenditure. The ARDL model was employed between the period of 1984 and 2019 to ascertain the link between the variables in question. The paper provides evidence that the long-run effects of health expenditure and institutional quality on economic growth are both surprisingly negative, but with only institutional quality having a statistically significant relationship. Further findings reveal that the institutional quality moderates the effect of health expenditure on growth. Specifically, when institutional quality is maintained at a threshold of 0.52 level, growth will be at least positive. This means that, with institutional quality at less than the threshold level, the economic growth will become negative. However, with the right policies in place as recommended, there could be a turn in events.